(Un)Becoming a Teacher: Negotiating Identities While Learning to Teach - Sumara, Dennis; Luce-Kapler, Rebecca (Canadian Journal of Education/Revue canadienne de l’éducation, 1996)
Becoming a teacher involves more than transposing teaching skills onto an already- established personal identity: it means including the identity “teacher” in one’s life. Beginning teachers must negotiate at least three teaching identities: those they bring with them into teacher education, those they develop while doing university course work, and those they develop during student teaching practicums. Because university and school experiences are generally only weakly connected for beginning teachers, the negotiation of these disparate teacher identities often remains unacknowledged and uninterpreted. By describing what happened when we used a “writerly” text in the teacher-education classroom, we show the importance of creating curricular locations for the interpretation of the teaching identities student teachers negotiate as they learn to teach. Devenir un enseignant implique plus que de simplement transposer des habiletés d’enseignement sur une identité personnelle déjà établie: cela signifie plutôt d’inclure l’identité “enseignant” dans la vie d’une personne. Les enseignants débutants doivent composer avec au moins trois identités reliées à l’enseignement: celles qu’ils amènent avec eux dans le cadre de la formation des maîtres, celles qu’ils développent en suivant des cours universitaires et celles qu’ils cultivent au cours de leurs stages en enseignement. Puisque les expériences du milieu scolaire et celles du milieu universitaire ne sont généralement que faiblement reliées pour les enseignants débutants, composer avec ces identités disparates demeure souvent un aspect non reconnu et non interprété. Les auteurs, en décrivant ce qui s’est produit lorsqu’ils ont utilisé un texte de type “littéraire” dans une classe de formation des maîtres, démontrent l’importance de créer une place dans les programmes universitaires pour l’interprétation des identités reliées à l’enseignement avec lesquelles les stagiaires composent pendant qu’ils apprennent à enseigner.